Low Dose Inflammatory Potential of Silica Particles in Human-Derived THP-1 Macrophage Cell Culture Studies – Mechanism and Effects of Particle Size and Iron - Premshekharan, Gayatri (Chem Biol Interact, 2017)
Silica and iron are major constituents in ambient particulate matter, and iron is a common impurity in many engineered nanomaterials. The purpose of this work was to determine the pro-inflammatory and other biological effects and mechanism of particle size and iron presence under low dose, non-cytotoxic conditions that are likely to approximate actual exposure levels, in contrast with higher dose studies in which cytotoxicity occurs. Specifically, human-derived THP-1 macrophages were exposed to 1 μg/ml of pristine and iron-coated 50 nm and 2 μm engineered silica nanoparticles. Particles were first characterized for size, size distribution, surface area, iron concentration, phase and aggregation in cell culture media. Then, biological assays were conducted to determine a non-lethal dose used in subsequent experiments. Superoxide production, lipid peroxidation, and increased pro-inflammatory cytokine (TNF-α and IL-1β) mRNA expression were measured as a function of particle size and iron presence. Smaller particle size and the presence of iron increased superoxide production, lipid peroxidation, and the induction of pro-inflammatory cytokine mRNA expression. Separate addition of an iron-chelator, a scavenger of superoxide and hydrogen peroxide, and an inhibitor of phosphatidylcholine specific phospholipase C (PC-PLC), suppressed the increase in cytokine mRNA expression. Furthermore, free iron itself showed none of the aforementioned effects. The results highlight the importance of particle size and iron in lung inflammation for both natural and engineered nanomaterials, under low dose, non-toxic conditions, and support the role of an oxidant, lipid peroxidation and PC-PLC dependent inflammatory mechanism.